Finite element analysis of hip implant with varying in taper neck lengths under static loading conditions. (September 2021) - Chethan, K.N.; Shyamasunder Bhat, N.; Zuber, Mohammad; Satish Shenoy, B
Highlights: von Mises stresses and total deformation under different loading conditions are used to evaluate the performance of the implant. ANSYS R-19.0 is used to evaluate Mises stresses, total deformation at head-neck junction with varying femoral head size, and taper lengths. Circular-shaped stem hip implants are used for the analysis with a stem length of 180 mm. The results revealed that the von Mises stresses in the complete implant tend to decrease with an increase in the femoral head size. Maximum 5% variation in stress values when 36mm femoral head is compared with 44 mm. Optimal taper length with an increase in the femoral head size is advised to consider to reduce the revision surgery rate. This study helps to evaluate the performance of circular-shaped hip implant using the von Mises stresses, total deformation at head-neck junction with varying femoral head size, and taper lengths using ANSYS R-19.0. Abstract: Background and objective: Total hip arthroplasty is known as one of the best advancements in orthopedics in the 20th century. Due to age or trauma hip joint has to replace by an artificial implant. After the hip arthroplasty, the patients can return to normal day-to-day activities with a normal range of motion. There are several types and designs are currently available. These designs usually depend upon the anatomy of the patients. There is a need for revision surgery due to dislocation and aseptic loosening in these joints over time in actively younger patients. Minor changes in the design stage can certainly improve the life expectancy of the implant and will also further reduce the revision rate. Methods: In this current work, finite element analysis is carried out by varying the neck length with a change in femoral head size for a circular-shaped stem. The effects of using a shorter neck are analyzed. A total of nine combinations are considered for analysis. Modeling is carried out in CATIA V-6 and analysis is performed in ANSYS R-19. A femoral head of 36, 40, and 44 mm and taper neck length of 18, 16, and 14 mm is considered. CoPE is considered as the material combination for all the models. Results: It was observed that the von Mises stresses in the complete implant tend to decrease with an increase in the femoral head size. Maximum 5% variation in stress values when 36 mm femoral head is compared with 44 mm. The stresses in the taper neck region tend to decrease with a decrease in the neck length. Minimum von Mises stress of 161.83 MPa was found for the complete implant and in the head-neck region, a minimum von Mises stress found 91.9 MPa. Conclusions: Performance evaluation of hip implant under static loading conditions gives a clear idea about the behavior of implant. It was found that a decrease in the von Mises stresses with a decrease in the taper length. However, these variations won't affect much in the performance of the hip implant. Also, a reduction in taper length can significantly increase the dislocation in the implant. So it is advised to consider the optimal taper length with an increase in the femoral head size.